Comparison of Antibacterial Activities of ProRoot MTA, OrthoMTA, and RetroMTA Against Three Anaerobic Endodontic Bacteria - Sedigheh Khedmat; Mohammad Aminipor; Maryam Pourhajibagher; Mohammad Javad Kharazifar; Abbas Bahador (Tehran University of Medical Sciences, 2018)
Objectives: The aim of this study was to assess the antibacterial activities of OrthoMTA, RetroMTA, and ProRoot MTA against Fusobacterium nucleatum (Fn), Porphyromonas gingivalis (Pg), and Prevotella intermedia (Pi). Materials and Methods: Each material was mixed on a glass slab using a spatula and was placed in columns containing the filter membrane of the modified membrane-enclosed immersion test (MEIT) system. The materials were sterilized after setting. The columns containing the sterilized test materials were placed in microcentrifuge tubes containing 500 µl of bacterial suspension. The systems were then incubated at 37°C under anaerobic conditions. After 72 hours, the bacterial growth and concentration (colony-forming unit (CFU)/ml) were assessed. The results were analyzed using one-way analysis of variance (ANOVA) and Tukey's post-hoc test in SPSS 22 software. In all analyses, the differences were considered significant at P<0.05. Results: OrthoMTA had the highest antibacterial activity against Pi. The mean number of CFU/ml of Fn in the presence of ProRoot MTA and RetroMTA was significantly lower than that in positive controls. There were significant differences between the antibacterial activities of ProRoot MTA and OrthoMTA against Pg compared to positive controls. Conclusions: ProRoot MTA, OrthoMTA, and RetroMTA had similar antibacterial activities against the three evaluated anaerobic endodontic bacteria, except RetroMTA against Pg.